Effect of Processing Methods on Nutritive and Antinutritive Properties of Seeds of Brachystegia eurycoma and Detarium microcarpum from Nigeria - Iweala, Emeka. E.J.; Uhegbu, Friday O.; Onwuchekwa, Chioma C.; Kanu, Ijeoma (Pakistan Journal of Nutrition, 2009)
Proximate analysis of the seeds of Brachystegia eurycoma and Detrarium microcarpum were carried out on both the dehulled and undehulled samples of the flour. The protein content of the seeds are quite low 9.1;7.2 and 11.4;8.2 for undehulled and dehulled Brachystegia eurycoma and Detarium microcarpum, respectively. Crude fibre is less than 3% in each, while ash was less than 5% each per 100gm dry weight of sample. Detarium microcarpum has a higher crude fat composition 18.5±0.03, 15.5±0.02 while Brachystegia eurycoma 15.5±0.04, 14.0±0.01 for the undehulled and dehulled samples respectively. Moisture content is higher in dehulled samples 14.3±0.01 and 16.7±0.03 for both seed types. The available carbohydrate is equally higher in the dehulled samples 59.0±0.01 and 57.0±0.01, respectively for both seeds. The sodium, potassium, calcium and magnesium contents were less than 1% each, with calcium having the highest concentration, followed by phosphorous. The phytochemical analysis showed the presence of alkaloids, tannins, saponins and flavonoids. Brachystegia eurcoma showed no presence of tannin. The findings are of nutritional relevance since these seeds are used for soup thickening by many homes in the southeastern Nigeria.